2018
DOI: 10.1007/s10488-018-0853-2
|View full text |Cite
|
Sign up to set email alerts
|

Unintended Consequences of Evidence-Based Treatment Policy Reform: Is Implementation the Goal or the Strategy for Higher Quality Care?

Abstract: This study examined patterns of evidence-based treatment (EBT) delivery following a county-wide EBT reform initiative. Data were gathered from 60 youth and their 21 providers, who were instructed to deliver therapy as they normally would under the EBT initiative. Results showed limited applicability of county-supported EBTs to this service sample, and that most youth did not receive traditional delivery of EBTs. Findings suggest that it may be unrealistic to expect providers to deliver EBTs with fidelity with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…This emphasizes the importance of implementation strategies being tailored to the different needs and views of providers in different phases of their careers, as the more experienced individuals might be more occupied with or affected by their cumulative experiences over time and how the intervention to be implemented interferes and balances with one’s usual everyday practice. When looking at the literature on important implementation strategies, both training issues and interventions that fit with real world context have been increasingly recognised as essential to target [18, 4345]. Developing training strategies, providing proper organizational support and securing intervention initiatives being appropriate for a given setting are not straightforward, given the complex multi-level challenges associated with implementation efforts [45, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasizes the importance of implementation strategies being tailored to the different needs and views of providers in different phases of their careers, as the more experienced individuals might be more occupied with or affected by their cumulative experiences over time and how the intervention to be implemented interferes and balances with one’s usual everyday practice. When looking at the literature on important implementation strategies, both training issues and interventions that fit with real world context have been increasingly recognised as essential to target [18, 4345]. Developing training strategies, providing proper organizational support and securing intervention initiatives being appropriate for a given setting are not straightforward, given the complex multi-level challenges associated with implementation efforts [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Such challenges are for instance associated with the differences between agency settings, the availability of resources, the multitude of different intervention components that are to be taught, the different needs of clinicians and the presenting problems of the clients [46]. This picture poses challenges on organizations planning intervention initiatives, for instance concerning which intervention(s) to implement and to what extent, as well the scaling of training needed [43]. It also poses both a need and encouragement for future research to continue address both which and how training efforts best can facilitate the uptake of new interventions and to secure that organizations lay grounds for learning environments fostering and motivating staff that are capable of delivering the intended service.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Dopp and colleagues [9] examined the ERIC compilation using the multilevel domains specified in the Consolidated Framework for Implementation Research (CFIR [10];) and found that most of the 73 strategies focus on changes in the individuals and systems (inner/outer setting) that will adopt a health services innovation, whereas only three seemed to address the possibility of tailoring the innovation to local contexts (i.e., "develop and implement tools for quality monitoring," "develop educational materials," and "promote adaptability"). Given that EBP usability is a key upstream determinant of implementation outcomes such as acceptability, appropriateness, and feasibility [11], as well as findings that context-specific modifications to EBPs are common and influential during implementation efforts [2,[12][13][14], current approaches to the promotion of implementation success are likely to be incomplete.…”
Section: Ongoing Challenges In Promoting Implementation Successmentioning
confidence: 99%
“…For EBPIs, this often involves requiring youth mental health service agencies to adopt wholesale a complex, expensive program without regard to its fit with their setting, clients, and available resources. A certain level of fidelity is likely necessary for any HSRP to produce its intended benefits, but intervention research has shown that “flexibility within fidelity” may actually produce better results than rigid adherence (Kendall et al 2008 ; Park et al 2018 ).…”
Section: Over-design and Under-design In Contemporary Hsrpsmentioning
confidence: 99%